Sintilimab Plus Bevacizumab Biosimilar Versus Sorafenib as First-Line Treatment for Unresectable Hepatocellular Carcinoma: A Cost-Effectiveness Analysis - Peng, Ye; Zeng, Xiaohui; Peng, Liubao; Liu, Qiao; Yi, Lidan; Luo, Xia; Li, Sini; Wang, Liting; Qin, Shuxia; Wan, Xiaomin; Tan, Chongqing (Frontiers in Pharmacology, 2022)
Objective: The ORIENT-32 clinical trial revealed that sintilimab plus bevacizumab biosimilar significantly improved the median progression-free survival (PFS) and median overall survival (OS) compared with sorafenib. This analysis evaluated the cost-effectiveness of sintilimab plus bevacizumab biosimilar as a first-line treatment for unresectable hepatocellular carcinoma from the Chinese perspective of healthcare system. Materials and methods: A Markov model with three mutual health states was constructed to evaluate the economic outcome of sintilimab plus bevacizumab biosimilar. The model cycle was 21 days and the simulation time horizon was a lifetime. The output parameters of the model were the total cost, life-year(LY), quality-adjusted LY (QALY), and incremental cost-effectiveness ratio (ICER). Sensitivity analyses were conducted to assess the robustness of the results. Results: The base-case results found that sintilimab plus bevacizumab biosimilar provided an improvement of 1.27 QALYs and 1.84 LYs compared with sorafenib, and ICER was $23,352/QALY. The HR for OS had the greatest influence on the ICER. The probability of sintilimab plus bevacizumab biosimilar was 85% at WTP thresholds of $30,552/QALY. Conclusions: The findings of this analysis suggested that sintilimab plus bevacizumab biosimilar was a cost-effective first-line therapy for patients with unresectable hepatocellular carcinoma.